Pengaruh Berbagai Antecedent dari Green Innovation terhadap Sustainable Performance - Herman Susanto; Edi Hamdi (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Sustainable development is seen as a key tool that has attracted attention from academics, politicians, leaders, and practitioners because of the growing demands from consumers on the environment, organizations, and companies. These entities can use green innovation as a main contribution to sustainable development. This study aims to examine the effect of green innovation as a mediator from green transformational leadership, ethical leadership, green organizational culture, and knowledge management on sustainable performance in construction companies in the Jabodetabek region. Using a quantitative approach and the Partial Least Structural Equation Modeling (PLS-SEM) analysis method, this research collects data from respondents working in the construction sector, with a total of 183 participants. The findings show that green innovation significantly mediates the impact of green transformational leadership, green organizational culture, and knowledge management on sustainable performance. However, ethical leadership does not have a significant effect on green innovation. These results highlight the importance of green innovation as a key link between green transformational leadership and green organizational culture with sustainable performance. The practical implications of this study suggest that construction companies need to develop green innovation through leaders who focus on well-planned project management, including scheduling, budgeting, and resource allocation, as well as monitoring cash flow, project financing, and cost control, which are essential for maintaining the company's financial health and project success.